PROBLEMS OF USING ARTIFICIAL INTELLIGENCE IN PHARMACEUTICAL COUNSELING (Uzbekistan Open Conference, 2026)
The article examines current challenges of integrating artificial intelligence (AI) technologies into pharmaceutical counseling practice. It identifies and systematizes the key problems associated with this integration: legal uncertainty in liability distribution, technical limitations of AI, data privacy risks, and ethical-social threats of dehumanizing care. A hybrid model is proposed as a solution, where AI serves as an assistant for routine tasks, while the pharmacist retains responsibility for complex clinical cases and empathetic patient interaction.